Achieving the gray to transparent switching electrochromic properties based on the diketopyrrolopyrrole, 3, 4-propylenedioxythiophene and thieno[3, 2-b]thiophene units. (15th July 2022) - Yue, Haoguo; Ming, Shouli; Du, Hongmei; Zhao, Jinsheng; Zhang, Yan
Graphical abstract: Highlights: Three soluble electrochromic polymers were chemically synthesized based on diketopyrrolopyrrole acceptor. PTPD-2 displayed color change from dark gray to transparent color in the p-type doping process. The three polymers exhibited favorable kinetic properties. Abstract: Electrochromic (EC) technology has attracted increasing attentions owing to their numerous advantages and extensive prospects. Here, the classic donor–acceptor (D-A) strategy was employed to design and synthesize three soluble polymers PTPD-1, PTPD-2, and PTPD-3, which was compatible with the current extensive requirements in the fields of EC conjugated polymers. Thereinto, diketopyrrolopyrrole was used as acceptor, 3, 4-propylenedioxythiophene and thieno[3, 2-b]thiophene were employed as donors. The influence of different feed ratios between donors and acceptors on the electrochemical, optical and EC performance of the three polymers were investigated in detail. The three polymers possess low oxidation potentials and optical band gaps (lower than 1.4 eV), and demonstrate different colors in the p-type doping process including greyish-green/dark gray/transparent color (PTPD-1), dark gray/gray/transparent color (PTPD-2) and green/light gray/transparent color (PTPD-3). Furthermore, all the three polymers show high optical contrasts (beyond 70% in the near infrared region), fast switching time and satisfying coloration efficiency. In conclusion, this study supplies a new structural design for the EC polymers switching between gray and transparent color, and can be beneficial to understand the EC behaviors of the D-A type conjugated polymers based on the DPP units.